2021
DOI: 10.3390/biomedicines9091178
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy, Mesenchymal Stem Cell Differentiation, and Secretion

Abstract: Mesenchymal stem cells (MSC) are multipotent cells capable to differentiate into adipogenic, osteogenic, and chondrogenic directions, possessing immunomodulatory activity and a capability to stimulate angiogenesis. A scope of these features and capabilities makes MSC a significant factor of tissue homeostasis and repair. Among factors determining the fate of MSC, a prominent place belongs to autophagy, which is activated under different conditions including cell starvation, inflammation, oxidative stress, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…Moreover, it has been shown that autophagy protects the cells from senescence [ 39 ], contributes to their rejuvenation [ 40 ], and shows a potential key contribution to hASCs’ therapeutic action [ 20 , 47 ] by providing a vital activity to cells. In fact, it has also been postulated that there is a relationship between autophagy and some signals that regulate the transduction mechanism directly involved in their differentiation [ 48 ], such as wingless/integrated (Wnt)/β-catenin, neurogenic locus notch homolog protein (Notch), and NF-E2-related factor 2 (Nrf2)-Kelch-like ECH-associated protein 1 (Keap1) signaling. All these autophagy functions on cells might represent an interesting way to improve the differentiation of hASCs for purposes of cartilage regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown that autophagy protects the cells from senescence [ 39 ], contributes to their rejuvenation [ 40 ], and shows a potential key contribution to hASCs’ therapeutic action [ 20 , 47 ] by providing a vital activity to cells. In fact, it has also been postulated that there is a relationship between autophagy and some signals that regulate the transduction mechanism directly involved in their differentiation [ 48 ], such as wingless/integrated (Wnt)/β-catenin, neurogenic locus notch homolog protein (Notch), and NF-E2-related factor 2 (Nrf2)-Kelch-like ECH-associated protein 1 (Keap1) signaling. All these autophagy functions on cells might represent an interesting way to improve the differentiation of hASCs for purposes of cartilage regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…This alkaloid has been used as therapeutic target against multiple diseases including amoebiasis (FDA approved), leukemia, Zikavirus, Ebolavirus, cytomegalovirus and SARS-CoV-2 infection (46-50), and was identified as an inhibitor regulating cell autophagy (46). Autophagy is an essential process for adipogenic differentiation (51). Inhibition of autophagy is of significant importance to alter differentiation state and metabolic function of adipocytes.…”
Section: Identification Of Two Novel Compounds That Inhibit Bmsc-deri...mentioning
confidence: 99%
“…MSCs are a heterogeneous cell population originating from the mesoderm in the early stage of embryonic development, 7 and include stem cells and differentiated progeny from the early stage of embryonic development and subsequent developmental stages. 8 As one of the most easily obtained primary cells, MSCs can be isolated from a variety of tissues, such as the umbilical cord, adipose tissue, dermis, tendons, bone marrow, muscles, and dental pulp.…”
Section: Introductionmentioning
confidence: 99%